Total Phenolic and Flavonoid Contents and Antioxidant Activity of Kembang Bulan Leaves (Tithonia diversifolia (Hemsley) A. Gray) - Noer Fauziah Rahman; Nursamsiar Nursamsiar; Megawati Megawati; Handayani Handayani; Christa A. M. Suares (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Many plants are used ethnomedicinally for the treatment of disease and restoration of health. One of these medicinal plants is Tithonia diversifolia. This study aims to determine the phenolic and flavonoid contents and antioxidant activity using the DPPH method from the leaves of T. diversifolia. Phenolic identification was carried out with FeCl3 reagent; the blackish green color formed indicates the presence of phenolic compounds. Identification of flavonoid was carried out using a reagent between magnesium powder and concentrated HCl; the orange-red color formed indicated the presence of flavonoid. Determination of phenolic and flavonoid contents from extract of T. diversifolia leaves was carried out colorimetrically using a UV-Vis spectrophotometer. The results showed that the Total Phenolic Contents (TPCs) of the ethyl acetate and ethanolic extract of the T. diversifolia leaves was 1.28 and 1.37% GAE, respectively, while the Total Flavonoid Contents (TFCs) was 2.21 and 3.41 mgQE/g, respectively. Better antioxidant activity was shown by the ethanol extract with an IC50 value of 84.018 µg/ml.Keywords: Antioxidant, flavonoid, phenolic, Tithonia diversifolia